2021
DOI: 10.1155/2021/6663233
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Mesoscale Analyses of Cement Stabilized Macadam Prepared by Vibratory and Nonvibratory Mixing Techniques

Abstract: The objective of this study is to analyze the effects of mixing techniques on the mechanical behavior and meso-structure of cement-treated aggregate. Different specimens were prepared by vibratory and nonvibratory mixing techniques. X-ray CT scans were performed to illustrate the distribution of cement mortar on aggregate. The strength, modulus, and fatigue tests under different stress states were tested to reveal the impacts of mixing techniques. Then, the relationships between strengths and loading rates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…According to these urgent problems, Jiang et al developed the vertical vibration compaction method (VVCM) to study the impact of different compaction methods on the performance of road materials. The test showed that the correlation between the specimens by the VVCM and the on-site drilling core sampling is as high as 92%, while the specimen’s mechanical properties and fatigue properties are superior to the general formation methods [ 20 , 21 , 22 , 23 , 24 , 25 ]. This paper presents a strong interlocked skeleton density-type cement-graded crushed stone using the VVCM moulding method to study the influence of different gradations, curing times, cement dosages and compaction coefficient on the mechanical properties of cement-graded crushed stone.…”
Section: Introductionmentioning
confidence: 99%
“…According to these urgent problems, Jiang et al developed the vertical vibration compaction method (VVCM) to study the impact of different compaction methods on the performance of road materials. The test showed that the correlation between the specimens by the VVCM and the on-site drilling core sampling is as high as 92%, while the specimen’s mechanical properties and fatigue properties are superior to the general formation methods [ 20 , 21 , 22 , 23 , 24 , 25 ]. This paper presents a strong interlocked skeleton density-type cement-graded crushed stone using the VVCM moulding method to study the influence of different gradations, curing times, cement dosages and compaction coefficient on the mechanical properties of cement-graded crushed stone.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the vibratory mixing method has been applied to improve the mechanical performance of different cement-based materials in China, such as steel fiber-reinforced concrete (SFRC) (Zheng et al, 2018), high-strength lightweight aggregate concrete (HSLWAC) (Luo et al, 2020;Xiong et al, 2019), and high-strength concrete (HSC) (Zhao et al, Zhao, Jiang, et al, 2019), especially cement-stabilized macadam (CSM) (Wang & Tan, 2021). Before this, the application of vibration in cement-based materials has proved its advantages on consolidating mixture (Liu et al, 2016;Zemam, 2020), reducing the internal friction force of fresh concrete (Safawi et al, 2004), and eliminating the voids and entrapped air present in the mixture (Koch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%